Commuter Travelers Perception of Toll Roads During the Ramp Up Period in Indonesia - Dharmawan, Weka Indra; Sjafruddin, Ade; Frazila, Russ Bona; Zukhruf, Febri (Institut Teknologi Bandung, 2023)
Abstract Studies on the travelers’ perceptions to toll roads during the ramp-up period are still rare, whereas they are important to assess toll road investment. The paper aims to establish a first approach in modeling the perceptions of individual commuter travelers during the learning process and adaptation to newly operating toll roads. Particularly, efforts to identify the attitudes and behaviors of individual commuter travelers towards interurban toll roads that connect between developing agglomeration areas. The data is collected through revealed and stated preference surveys using a snowball sampling technique with social media applications. Then we develop a binary logit model to explore commuter travelers’ perceptions to toll road during ramp-up period, and the results indicate that when doing commuter travel activities prefer to use the toll road, with the attributes that most influence on decision making respectively, travel time, travel costs, toll gate distance, travel distance, traveler's age, scenic beauty and the frequency of using toll roads. The paper also showed that the positive preference of toll roads during the ramp-up period is not always related to traffic congestion such as in dense urban areas, the presence of sightseeing traffic is very potential. Keywords: Route choice behavior, binary logit model, toll road, ramp-up period Abstrak Studi mengenai persepsi masyarakat terhadap jalan tol selama periode ramp-up masih jarang dilakukan, hal ini penting untuk menilai kelayakan investasinya. Makalah ini bertujuan untuk menetapkan pendekatan pertama dalam memodelkan persepsi individu pelaku perjalanan komuter selama periode tersebut sebagai proses belajar dan beradaptasi terhadap jalan tol yang baru beroperasi. Khususnya, upaya untuk mengidentifikasi sikap dan perilaku individu pelaku perjalanan terhadap jalan tol antar kota penghubung kawasan aglomerasi yang sedang berkembang. Pengumpulan data dilakukan melalui survei revealed dan stated preference dengan teknik bola salju (snowball sampling) yang menggunakan media sosial. Kemudian kami mengembangkan model logit-biner untuk mengeksplorasi persepsi penumpang komuter terhadap jalan tol pada periode ramp-up dan hasilnya menunjukkan bahwa ketika melakukan aktivitas perjalanan, pelaku perjalanan komuter lebih memilih menggunakan jalan tol dengan atribut yang paling berpengaruh terhadap pengambilan keputusan masing-masing adalah, waktu tempuh, biaya perjalanan, jarak gerbang tol, jarak tempuh, umur penumpang, keindahan pemandangan dan frekuensi penggunaan jalan tol. Makalah ini juga menunjukkan bahwa preferensi positif terhadap jalan tol pada periode ramp-up tidak selalu terkait dengan kemacetan lalu lintas seperti di wilayah perkotaan yang padat, keberadaan lalu lintas tamasya sangat potensial mempengaruhi. Kata-kata kunci: Perilaku pemilihan rute, model logit-biner, jalan tol, periode ramp-up